GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS OF ROOT OF AN ECONOMICALLY IMPORTANT PLANT, CENCHRUS CILIARIS L. FROM THAR DESERT, RAJASTHAN (INDIA) - Arora, Sunita; Kumar, Ganesh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The study was carried out with an objective to characterize the possible bioactive phytochemical constituents from the root of Cenchrus ciliaris L. using various solvents of different polarities, i.e., methanol, ethyl acetate, and hexane by gas chromatography-mass spectroscopy (GC-MS) analysis. Methods: Plant material was collected from harsh, xeric conditions of Tharâ€ during August to October. The shade-dried plant root powder was extracted with solvents using Soxhlet extractor. The phytochemical compounds were investigated using PerkinElmer GC-MS, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology and Willey 8 library. Results: Maximum % area is found for stigmasta-5,22-dien-3-ol and present in maximum amount (12.68%) with reaction time (RT)=36.461 minutes in the methanolic extract. 1,2,3-propanetriol, 1-acetate is present in maximum amount (13.15%) with RT=6.582 minutes in the ethyl acetate extract. Tetracontane is present in maximum amount (16.70%) with RT=18.744 minutes in the hexane extract of root of C. ciliaris L. Conclusions: Green plants synthesize and preserve a variety of biochemical compounds. Plant secondary metabolites are commercially important and are used by pharmaceutical industry as well as the traditional practitioners. The GC-MS study helps to predict the formula and structure of phytoconstituents that can be used for drug design, and further investigation may lead to the development of various drug formulations. Â